All-solid-state battery and application thereof
By forming a protective layer with high interfacial energy, high ion conduction and high flexibility on the surface of the lithium metal negative electrode, and combining the use of sulfide solid electrolyte, the dendrite formation and instability problems during the charging and discharge of lithium metal batteries is solved, and the long cycle performance and safety improvement of all solid state batteries is achieved.
Patent Information
- Application Number
- CN202411828324.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Lithium metal batteries are prone to form dendrites during charging and discharging, resulting in short circuits and degradation of battery performance. The instability of lithium metal in electrolyte will cause side reactions, reducing the cycle life and safety of the battery.
A protective layer is formed on the surface of the lithium metal negative electrode. The protective layer has high interface energy, high ion conductivity and high flexibility, enhancing the interface stability between the lithium metal negative electrode and the solid electrolyte, and using sulfide solid electrolyte in combination.
Effectively inhibit the formation of lithium dendrites, promote the rapid transmission and uniform deposition of lithium ions, improve the cycle stability and safety of the battery, and obtain a full-solid-state battery with long-cycle performance.
Smart Images

Figure CN119627197A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to an all-solid-state battery and applications thereof. Background Art
[0002] In recent years, with the increasing demand for electric vehicles, portable electronic devices and renewable energy storage, lithium metal batteries have attracted widespread attention due to their high energy density. Lithium metal batteries have the potential to provide higher energy density than traditional lithium-ion batteries, but lithium metal is prone to form dendrites during charging and discharging, resulting in short circuits and battery performance degradation. In addition, the instability of lithium metal in the electrolyte can trigger side reactions, reducing the cycle life and safety of the battery.
[0003] In order to solve the above problems, solid electrolytes are used, electrode surfaces are modified, and interface protection layers are added. However, there are problems such as the stability of solid electrolytes, poor compatibility of modified electrodes, low ion conductivity, single function, and adverse reactions, which further affect battery performance. Summary of the invention
[0004] The present invention proposes an all-solid-state battery and its application. Through the all-solid-state battery and its application provided by the present invention, a protective layer can be formed on the surface of the lithium metal negative electrode. The protective layer has high interface energy, high ion conductivity and high flexibility, and can enhance the interface stability between the lithium metal negative electrode and the solid electrolyte, reduce the occurrence of side reactions, and is used in combination with the sulfide solid electrolyte provided by the present application to obtain an all-solid-state battery with long cycle performance.
[0005] To solve the above technical problems, the present invention is implemented through the following technical solutions.
[0006] The present invention provides an all-solid-state battery, comprising at least:
[0007] Positive electrode;
[0008] A lithium metal negative electrode, wherein the surface of the lithium metal negative electrode has a protective layer; and
[0009] A solid electrolyte membrane is arranged between the positive electrode plate and the lithium metal negative electrode, and the solid electrolyte membrane includes a sulfide solid electrolyte.
[0010] In one embodiment of the present invention, the protective layer includes lithium fluoride, lithium nitride and a flexible polymer.
[0011] In an embodiment of the present invention, the thickness of the protective layer is 0.01 μm to 20 μm.
[0012] In one embodiment of the present invention, the protective layer is obtained by the following method:
[0013] Dissolve 3-(trifluoromethoxy)benzylamine in a solvent to obtain a modified solution; and
[0014] Coat the modified solution on the surface of lithium metal, and then dry it in vacuum to obtain the protective layer.
[0015] In an embodiment of the present invention, the solvent is selected from one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol diisobutyl ether, or ethylene glycol diacetate, and the content of 3-(trifluoromethoxy)benzylamine in the modified solution is 0.1 wt% to 10 wt%.
[0016] In an embodiment of the present invention, the coating method includes one or more of dip coating, blade coating, spray coating, spin coating, brush coating, roll coating, or drop coating, the temperature of the vacuum drying is 10°C to 150°C, and the drying time is 0.1 h to 24 h.
[0017] In an embodiment of the present invention, the chemical formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb; X is selected from one or more of Cl, Br, or I.
[0018] In an embodiment of the present invention, M is selected from one or more of Sb, In, or Bi, X is selected from Cl, and the value range of b is 0 < b ≤ 0.1.
[0019] In an embodiment of the present invention, the chemical formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb; Q is selected from one or more of Cl, Br, or I.
[0020] In an embodiment of the present invention, E is selected from Mg, Q is selected from Cl, and the value range of g is 0.01 ≤ g ≤ 0.1.
[0021] The present invention also provides an electronic device including the all-solid-state battery described above.
[0022] In summary, the present invention proposes an all-solid-state battery and its application, which forms a protective layer on the surface of the lithium metal negative electrode, and the protective layer has high interface energy, high ion conductivity and high flexibility at the same time, which can effectively maintain the interface stability of the lithium metal negative electrode / solid electrolyte, ensure a continuous and stable lithium ion transmission channel, reduce the interface impedance, and improve the charge transfer efficiency. It can inhibit the formation of lithium dendrites, promote the rapid transmission and uniform deposition of lithium ions, and when used in combination with the sulfide solid electrolyte provided by the present application, it can achieve a stable cycle of the sulfide solid electrolyte-lithium metal battery, and obtain an all-solid-state battery with long cycle performance. The formed protective layer has a protective layer with good chemical and thermal stability, enhances the interface stability between the lithium metal negative electrode and the solid electrolyte, reduces the occurrence of side reactions, and the preparation method is simple, which can reduce the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0024] Figure 1 The 1C / 1C long cycle performance diagram at room temperature for the all-solid-state battery in Example 3. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0027] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] The present invention proposes an all-solid-state battery, which includes a positive electrode plate, a lithium metal negative electrode and a solid electrolyte membrane, wherein the surface of the lithium metal negative electrode has a protective layer, the solid electrolyte membrane is arranged between the positive electrode plate and the lithium metal negative electrode, and the solid electrolyte membrane includes a sulfide solid electrolyte. In the present invention, the all-solid-state battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type and type of the all-solid-state battery.
[0029] In one embodiment of the present invention, the protective layer includes, for example, lithium fluoride, lithium nitride and flexible polymers. By forming a protective layer on the surface of the lithium metal negative electrode, the interface stability of the lithium metal / solid electrolyte can be effectively maintained, and the formation of lithium dendrites can be inhibited, thereby promoting the rapid transmission and uniform deposition of lithium ions, and realizing the stable cycle of the sulfide solid electrolyte-lithium metal battery.
[0030] In one embodiment of the present invention, the thickness of the protective layer is, for example, 0.01 μm to 20 μm. If the protective layer is too thin, it cannot effectively maintain the interface stability of the lithium metal anode / solid electrolyte and inhibit the formation of lithium dendrites, which is insufficient to improve the performance of the all-solid-state battery. If the protective layer is too thick, it will hinder the lithium ion (Li + ) transmission, thus affecting battery performance.
[0031] In one embodiment of the present invention, the protective layer is obtained by the following method:
[0032] dissolving 3-(trifluoromethoxy)benzylamine in a solvent to obtain a modified solution;
[0033] The modified solution is coated on the surface of lithium metal and then dried in vacuum to obtain a protective layer.
[0034] In one embodiment of the present invention, the solvent is selected from one or more of ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEEE), ethylene glycol diisobutyl ether (DIBE) or ethylene glycol diacetate (DEGEE), and when 3-(trifluoromethoxy)benzylamine (C8H8F3NO) is dissolved in the solvent, the temperature range of the solvent is controlled to be, for example, 25° C. to 100° C. The content of 3-(trifluoromethoxy)benzylamine (C8H8F3NO) in the modified solution is, for example, 0.1wt% to 10wt% to ensure the thickness of the protective layer.
[0035] In one embodiment of the present invention, the modified solution is coated on the surface of lithium metal by one or more methods such as dipping, scraping, spraying, spin coating, brushing, rolling or dripping, etc. The lithium metal is, for example, a lithium sheet, etc. The vacuum drying temperature is, for example, 10°C to 150°C, and the drying time is, for example, 0.1h to 24h. By in-situ synthesis, a protective layer with good chemical and thermal stability is formed to enhance the interfacial stability between the lithium metal negative electrode and the solid electrolyte and reduce the occurrence of side reactions. And the preparation method is simple, which can reduce the production cost.
[0036] In one embodiment of the present invention, the F element and the N element in 3-(trifluoromethoxy)benzylamine react with lithium metal to generate in situ lithium fluoride (LiF) and lithium nitride (Li3N), wherein LiF has high interfacial energy and electronic insulation properties, can effectively maintain the stability of the lithium metal negative electrode / solid electrolyte interface, and inhibit the formation of lithium dendrites. Li3N promotes the rapid transmission and uniform deposition of lithium ions by virtue of its excellent ionic conductivity. The unreacted 3-(trifluoromethoxy)benzylamine solution can generate a thin flexible polymer layer on the surface of lithium metal, which can not only enhance the contact between the lithium metal negative electrode and the solid electrolyte membrane, but also can continuously generate LiF and Li3N during the charge and discharge process of the sulfide solid electrolyte-lithium metal battery to maintain the integrity of the protective layer. By forming a multifunctional lithium metal protective layer including LiF, Li3N and flexible polymer on lithium metal, the protective layer has high interface energy, high ion conductivity and high flexibility. The three substances work synergistically to achieve a good lithium metal anode / solid electrolyte interface and improve the stable cycle of sulfide solid electrolyte-lithium metal battery.
[0037] In one embodiment of the present invention, the solid electrolyte membrane includes, for example, a sulfide solid electrolyte, which can improve the interface stability between the solid electrolyte membrane and the lithium metal negative electrode, ensure a continuous and stable lithium ion transmission channel, reduce the interface impedance, and improve the charge transfer efficiency. Specifically, the chemical formula of the sulfide solid electrolyte is selected from Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z At least one of the following. a P 1-b M b S c O d X eAmong them, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb, etc., and X is selected from at least one of Cl, Br, I, etc. Further, M is, for example, selected from at least one of Sb, In, or Bi, X is Cl, and the value range of b is, for example, 0 < b ≤ 0.1. Further still, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of elements M and X and the value range of b in the sulfide solid electrolyte, the stability of the sulfide solid electrolyte can be improved, the cycling performance of the battery can be improved, and thus the service life of the battery can be extended.
[0038] In an embodiment of the present invention, when the chemical formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q z wherein, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, etc., and Q is selected from at least one of Cl, Br, I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the types of elements E and Q and the value range of g in the sulfide solid electrolyte, the stability of the sulfide solid electrolyte can be improved, the cycling performance of the battery can be improved, and thus the service life of the battery can be extended.
[0039] In an embodiment of the present invention, when preparing the sulfide solid electrolyte, in an atmosphere of an inert gas such as argon, according to the chemical formula Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z, after the Li source, P source, M source, S source and X source, or the Li source, P source, E source, S source and Q source are uniformly mixed according to stoichiometric ratio, for example, placed in a ball mill for ball milling to obtain a precursor powder, and then the precursor powder is annealed and sintered at a high temperature to obtain a sulfide solid electrolyte. Wherein, the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of simple substance P, P2S5, P4S6, PCl5 or PBr5, the M source is selected from one or more of M oxides or M sulfides, the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, the E source is selected from one or more of E oxides or E sulfides, the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, the S source is selected from one or more of simple substance S, Li2S, P2S5, M sulfide or E sulfide, and the O element in the chemical formula comes from the oxide of M or the oxide of E. Wherein, the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1000 rpm, and the ball milling time is, for example, 1 h to 48 h. After ball milling, a precursor powder is obtained, and the precursor powder is calcined at 400° C. to 600° C. for 1 h to 18 h to obtain a sulfide solid electrolyte.
[0040] In one embodiment of the present invention, the solid electrolyte membrane is obtained by, for example, cold pressing the above-mentioned sulfide solid electrolyte at a pressure of 300 MPa to 400 MPa, and the thickness of the solid electrolyte membrane is, for example, 100 μm to 500 μm.
[0041] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric, and the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.
[0042] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, an electrolyte, a conductive agent, and a binder, wherein the positive electrode active material is, for example, selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO), or lithium nickel cobalt aluminum oxide (NCA), the electrolyte is, for example, a halide solid electrolyte, the conductive agent is, for example, selected from at least one of graphite, graphene, conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF), or carbon nanotubes, and the binder is, for example, selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (MMA ... Methacrylate, PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane (PU), polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer (EPDM), styrene-butadiene rubber, fluorine rubber (Fluororubber), β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (Ethylene-chlorotrifluoroethylene copolymer, ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE).
[0043] In one embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, electrolyte such as Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the binder is, for example, PTFE. After the positive electrode active material, electrolyte, conductive agent and binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, they are compounded with aluminum foil by dry pressing to obtain a positive electrode sheet. The present invention does not limit the mass ratio of the positive electrode active material, electrolyte, conductive agent and binder, which can be selected according to actual needs, and the positive electrode current collector can be not provided according to needs.
[0044] In one embodiment of the present invention, the above-mentioned positive electrode plate, solid electrolyte membrane and lithium metal negative electrode are placed in sequence, pressed and sealed, and an all-solid-state battery is obtained. The assembly process of the all-solid-state battery is completed in a glove box with an inert atmosphere. The all-solid-state lithium metal battery assembled using the lithium metal negative electrode with a multifunctional protective layer will not have obvious dendrite growth problems, and alleviates the interface reaction problem between the sulfide solid electrolyte and the lithium metal negative electrode, effectively improving the cycle stability of the sulfide solid electrolyte all-solid-state lithium metal.
[0045] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0046] Example 1
[0047] Preparation of solid electrolyte membrane: Under argon atmosphere, 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 raw materials were added into a ball mill with a ball-to-material ratio of 30:1 and a rotation speed of 500 rpm for 20 h. Then, the precursor powder obtained by ball milling was sintered at 500 °C for 10 h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide solid electrolyte. Cold pressing at a pressure of 350 MPa yields a 300 μm thick solid electrolyte membrane.
[0048] Preparation of positive electrode: LiNi0.8 Co 0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , PTFE are mixed evenly in a mass ratio of 69:29:1:1, and then compounded with aluminum foil by dry pressing, and cut into discs with a diameter of 10 mm to obtain a positive electrode sheet. The conductive agent includes Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1.
[0049] Preparation of lithium metal negative electrode: 3-(trifluoromethoxy)benzylamine was dissolved in DME at 25°C to obtain a modified solution with a content of 0.1wt%. The modified solution was coated on the surface of the lithium sheet and then vacuum dried at 60°C for 5h to obtain a lithium metal negative electrode with a multifunctional in-situ protective layer.
[0050] All-solid-state battery assembly: The prepared positive electrode sheet, solid electrolyte membrane and lithium metal negative electrode are stacked in sequence, pressed and sealed, and assembled into an all-solid-state battery.
[0051] Example 2
[0052] The content of 3-(trifluoromethoxy)benzylamine in the modified solution was 1 wt %, and other operations were consistent with those in Example 1.
[0053] Example 3
[0054] The content of 3-(trifluoromethoxy)benzylamine in the modified solution was 2 wt %, and other operations were consistent with those in Example 1.
[0055] Example 4
[0056] The content of 3-(trifluoromethoxy)benzylamine in the modified solution was 5 wt %, and other operations were consistent with those in Example 1.
[0057] Example 5
[0058] The content of 3-(trifluoromethoxy)benzylamine in the modified solution was 10 wt %, and other operations were consistent with those in Example 1.
[0059] Example 6
[0060] 3-(trifluoromethoxy)benzylamine was dissolved in DEEE solvent, and other operations were consistent with Example 3.
[0061] Example 7
[0062] 3-(trifluoromethoxy)benzylamine was dissolved in DIBE solvent, and other operations were consistent with Example 3.
[0063] Example 8
[0064] 3-(trifluoromethoxy)benzylamine was dissolved in DEGEE solvent, and other operations were consistent with Example 3.
[0065] Example 9
[0066] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Sb2O5 is Li 5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 , other operations remain the same as those in Example 3.
[0067] Example 10
[0068] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5 is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.
[0069] Embodiment 11
[0070] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5 is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 , other operations remain the same as those in Example 3.
[0071] Example 12
[0072] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.48 mol of P2S5, and 0.02 mol of Sb2O5 is Li 5.5 P 0.96 Sb 0.04 S4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.
[0073] Example 13
[0074] The chemical formula of the sulfide solid electrolyte prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol In2O3 is Li 5.52 P 0.99 In 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.
[0075] Embodiment 14
[0076] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.
[0077] Embodiment 15
[0078] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol In2O3 is Li 5.62 P 0.94 In 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.
[0079] Example 16
[0080] The chemical formula of the sulfide solid electrolyte prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol In2O3 is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.
[0081] Embodiment 17
[0082] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 , other operations remain the same as those in Example 3.
[0083] Embodiment 18
[0084] The chemical formula of the sulfide solid electrolyte prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol Bi2O3 is Li 5.52 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.
[0085] Embodiment 19
[0086] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.
[0087] Embodiment 20
[0088] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol Bi2O3 is Li 5.62 P 0.94 Bi 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.
[0089] Embodiment 21
[0090] The chemical formula of the sulfide solid electrolyte prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol Bi2O3 is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.
[0091] Embodiment 22
[0092] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 , other operations remain the same as those in Example 3.
[0093] Embodiment 23
[0094] The chemical formula of the sulfide solid electrolyte prepared by 2.015 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.01 mol MgO is Li 5.53 P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 , other operations remain the same as those in Example 3.
[0095] Embodiment 24
[0096] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 3.
[0097] Embodiment 25
[0098] The chemical formula of the sulfide solid electrolyte prepared by 2.09 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.06 mol MgO is Li 5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 3.
[0099] Embodiment 26
[0100] The chemical formula of the sulfide solid electrolyte prepared by 2.15 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.1 mol MgO is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 , other operations remain the same as those in Example 3.
[0101] Embodiment 27
[0102] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I0 .1 , other operations remain the same as those in Example 3.
[0103] Comparative Example 1
[0104] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 3.
[0105] Comparative Example 2
[0106] The lithium metal negative electrode was replaced with a lithium sheet. Other operations were the same as in Example 1.
[0107] Comparative Example 3
[0108] The content of 3-(trifluoromethoxy)benzylamine in the modified solution was 20 wt %, and other operations were consistent with those in Example 1.
[0109] In Examples 1-27 and Comparative Examples 1-3 of the present invention, different sulfide solid electrolytes and lithium metal negative electrodes are used to prepare all-solid-state batteries. Some preparation conditions and performances of the sulfide solid electrolytes are shown in Table 1. Under a 25°C environment, the above-prepared all-solid-state battery is subjected to long-cycle charge and discharge, its discharge capacity is measured, and the energy density is calculated. Among them, the operating voltage range of the battery test is 2.5V-4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded, which is the 1C discharge capacity. When the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH), the test is terminated, and the number of cycles at room temperature is obtained. The test results are shown in Table 2.
[0110] Table 1. Properties of sulfide solid electrolyte and lithium metal negative electrode in Examples 1-27 and Comparative Examples 1-3
[0111]
[0112] Table 2 Performance test results of all-solid-state batteries in Examples 1-27 and Comparative Examples 1-3
[0113]
[0114] Please refer to Table 1 and Table 2. By comparing Examples 1-5 and Comparative Examples 2-3, it can be seen that as the content of C8H8F3NO in the modified solution increases, the protective layer of the lithium metal negative electrode becomes thicker and thicker, and the cycle performance of the all-solid-state battery gradually increases and then gradually decreases. This is because the addition of the protective layer can regulate the deposition of Li and inhibit the growth of lithium dendrites, but when the protective layer is too thick, it will hinder the Li + transmission, thus affecting battery performance.
[0115] Please refer to Table 1 and Table 2. By comparing Example 3 and Examples 6-8, it can be seen that when different solvents are used in the modified liquid, the cycle performance of the all-solid-state battery is similar, and when the DME solution is used, the battery performance is optimal.
[0116] See also Figure 1 As shown, at a current density of 1C, the all-solid-state battery in Example 3 still has an energy storage capacity of about 145mAh / g after 1452 cycles, indicating that the combination of sulfide solid electrolyte and lithium metal negative electrode enables the all-solid-state battery to have excellent specific capacity, rate performance and long cycle life.
[0117] Please refer to Table 1 and Table 2. It can be seen from Examples 3 and 9-11 that as the doping amount of the Sb element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery gradually increases and then gradually decreases. It can be seen from Examples 13-16 that as the doping amount of the In element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery gradually increases and then gradually decreases. It can be seen from Examples 18-21 that as the doping amount of the Bi element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery first increases gradually and then gradually decreases. It can be seen from Examples 23-26 that as the doping amount of the Mg element in the sulfide solid electrolyte increases, the cycle performance of the all-solid-state battery first increases gradually and then gradually decreases. This is because when the doping amount in the sulfide solid electrolyte is too low, the improvement effect of the stability of the sulfide solid electrolyte itself is not obvious, and the cycle performance is poor. When the doping amount in the sulfide solid electrolyte is too large, excessive doping will cause excessive lattice distortion, destroy the original crystal structure, and may cause the structural stability of the material to decrease, and the cycle performance of the battery to decrease. Therefore, controlling the doping amount in the sulfide solid electrolyte within an appropriate range and matching it with a lithium metal negative electrode can improve the cycle performance of the all-solid-state battery.
[0118] Please refer to Table 1 and Table 2. Comparing Examples 3 and 12, Examples 14 and 17, Examples 19 and 22, and Examples 24 and 27, it can be seen that when the doping amount of Sb, In, Bi or Mg in the sulfide solid electrolyte is the same, the addition of Br and I elements will reduce the cycle performance of the battery. Comparing Example 3, Example 14, Example 19, Example 24 and Comparative Example 1, it can be seen that when the sulfide solid electrolyte is not doped with elements such as Sb, In, Bi or Mg, the cycle performance of the battery is very poor. Therefore, when the lithium metal negative electrode in the present application and the sulfide solid electrolyte provided in the present application are used in combination, the cycle performance of the all-solid-state battery can be greatly improved.
[0119] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.
[0120] In summary, the present invention proposes an all-solid-state battery and its application, which forms a protective layer on the surface of the lithium metal negative electrode, and the protective layer has high interface energy, high ion conductivity and high flexibility at the same time, which can effectively maintain the interface stability of the lithium metal negative electrode / solid electrolyte, ensure a continuous and stable lithium ion transmission channel, reduce the interface impedance, and improve the charge transfer efficiency. It can inhibit the formation of lithium dendrites, promote the rapid transmission and uniform deposition of lithium ions, and when used in combination with the sulfide solid electrolyte provided by the present application, it can achieve a stable cycle of the sulfide solid electrolyte-lithium metal battery, and obtain an all-solid-state battery with long cycle performance. The formed protective layer has a protective layer with good chemical and thermal stability, enhances the interface stability between the lithium metal negative electrode and the solid electrolyte, reduces the occurrence of side reactions, and the preparation method is simple, which can reduce the production cost.
[0121] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0122] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. An all-solid-state battery, characterized in that: At least: Positive electrode; A lithium metal negative electrode, wherein the surface of the lithium metal negative electrode has a protective layer; as well as A solid electrolyte membrane is arranged between the positive electrode plate and the lithium metal negative electrode, and the solid electrolyte membrane includes a sulfide solid electrolyte.
2. The all-solid-state battery according to claim 1, characterized in that: The protective layer includes lithium fluoride, lithium nitride and a flexible polymer.
3. The all-solid-state battery according to claim 1, characterized in that: The thickness of the protective layer is 0.01 μm to 20 μm.
4. The all-solid-state battery according to claim 1, characterized in that: The protective layer is obtained by the following method: dissolving 3-(trifluoromethoxy)benzylamine in a solvent to obtain a modified solution; as well as The modified solution is coated on the surface of the lithium metal and then dried in vacuum to obtain the protective layer.
5. The all-solid-state battery according to claim 4, characterized in that: The solvent is selected from one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol diisobutyl ether or ethylene glycol diacetate, and the content of 3-(trifluoromethoxy)benzylamine in the modified solution is 0.1wt% to 10wt%.
6. The all-solid-state battery according to claim 4, characterized in that: The coating method includes one or more of dipping, scraping, spraying, spin coating, brushing, rolling or dripping. The vacuum drying temperature is 10° C. to 150° C., and the drying time is 0.1 h to 24 h.
7. The all-solid-state battery according to claim 1, characterized in that: The chemical formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb; X is selected from one or more of Cl, Br or I.
8. The all-solid-state battery according to claim 7, characterized in that: M is selected from one or more of Sb, In or Bi, X is selected from Cl, and the value range of b is 0 <b≤0.1。 9. The all-solid-state battery according to claim 1, characterized in that: The chemical formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb; Q is selected from one or more of Cl, Br or I.
10. The all-solid-state battery according to claim 9, characterized in that: E is selected from Mg, Q is selected from Cl, and the value range of g is 0.01≤g≤0.
1.
11. An electronic device, characterized in that: An all-solid-state battery comprising any one of claims 1-10.
Citation Information
Patent Citations
High energy density all solid state battery based on sulfide solid electrolyte
CN110429281A
Modified lithium metal negative electrode, preparation method thereof and application of modified lithium metal negative electrode in all-solid-state lithium metal battery
CN115799451A
Lithium negative electrode with LiF-Li3N multifunctional interface layer and preparation method of lithium negative electrode
CN115939320A
Preparation method and application of lithium argyrodite type solid electrolyte and sulfide film
CN117457972A
Vulcanized electrolyte and preparation method thereof, composition for composite electrolyte membrane, method for preparing composite electrolyte membrane, and lithium ion battery
CN118289807A
Cited By
Negative electrode for sulfide all-solid-state lithium metal battery, preparation method and battery
CN121662774A